PROFITABILITY OF SMALLHOLDER DAIRY FARMS BASED ON THE PERFORMANCE OF LACTATING COWS AND FRESH MILK MARKET PRICES AT LOWLAND AREAS OF YOGYAKARTA - Widiati, R.; Adiarto, A.; Hertanto, B.S. (Diponegoro University, 2012)
This study was aimed to determine the profitability of smallholder dairy farmers at the lowlandareas of Yogyakarta related to dairy cow performance (milk production) to be achieved at various freshmilk market prices. Thirty lactating Holstein cows belonging to the 16 farmers at the lowland areas ofYogyakarta Province selling milk directly to the consumers were drawn as the samples. Profitability wasdetermined by enterprise budgeting (accounting profit and economic profit) and break even point. Inputand output data were obtained from interview with the farmer samples along with direct observations onthe cows performance. The results indicated that under the observed condition of 9.28 liter/day averagemilk production at IDR 4,700 market price, the accounting profit was found to be IDR7,758,862/lactating cow/year. The farmers were able to make an economic profit of IDR 1,839,875 withprofit margin index of 0.12. If the farmers have to sell the fresh milk to the Cooperatives at the price ofIDR 2.800 or IDR 3.200/liter, in order to gain a positive economic profit, milk production must be atleast 13.5 or 12.0 liters/day, respectively.